2021
DOI: 10.1074/jbc.ra120.015779
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis drives photoreceptor degeneration in mice with defects in all-trans-retinal clearance

Abstract: The death of photoreceptor cells in dry age-related macular degeneration (AMD) and autosomal recessive Stargardt disease (STGD1) is closely associated with disruption in all- trans -retinal (atRAL) clearance in neural retina. In this study, we reveal that the overload of atRAL leads to photoreceptor degeneration through activating ferroptosis, a nonapoptotic form of cell death. Ferroptosis of photoreceptor cells induced by atRAL resulted from increased ferrous ion (Fe 2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 74 publications
(134 reference statements)
3
42
0
Order By: Relevance
“…Moreover, GSDME-N translocates to the mitochondria where it aggregates and perforates mitochondrial membranes, which in turn accentuates pyroptosis and apoptosis through enhancing Cyt c release and caspase-3 activation. In light of current and previous studies, we conclude that photoreceptor damage by atRAL is bound up with apoptosis(6), ferroptosis (7) and pyroptosis, but is independent of necroptosis. Due to the identification of GSDME but not GSDMD as an executioner of pyroptosis and an amplifier of apoptosis in photoreceptors suffering from atRAL accumulation, GSDME may be an efficient and promising target for the therapy of photoreceptor degeneration in patients with dry AMD and STGD1.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Moreover, GSDME-N translocates to the mitochondria where it aggregates and perforates mitochondrial membranes, which in turn accentuates pyroptosis and apoptosis through enhancing Cyt c release and caspase-3 activation. In light of current and previous studies, we conclude that photoreceptor damage by atRAL is bound up with apoptosis(6), ferroptosis (7) and pyroptosis, but is independent of necroptosis. Due to the identification of GSDME but not GSDMD as an executioner of pyroptosis and an amplifier of apoptosis in photoreceptors suffering from atRAL accumulation, GSDME may be an efficient and promising target for the therapy of photoreceptor degeneration in patients with dry AMD and STGD1.…”
Section: Discussionsupporting
confidence: 64%
“…After being washed by PBS three times, fluorescence micrographs were taken using the Leica DM2500 microscope. TEM TEM analysis of mitochondrial ultrastructures in WT or Gsdme −/− 661W photoreceptor cells incubated with 5-μM atRAL for 6 h was performed as previously described (7).…”
Section: Sytox® Orange Stainingmentioning
confidence: 99%
See 2 more Smart Citations
“…Ferroptosis is a regulated cell death driven by iron-dependent lipid peroxidation ( Dixon et al, 2012 ). Elevated Fe 2+ promotes the generation of lipid peroxidation and ROS ( Chen et al, 2020 ). We found that in WDR45 MT expressing cells, the content of MDA (an end product of lipid peroxidation) and ROS was significantly increased ( Figures 4A,B ).…”
Section: Resultsmentioning
confidence: 99%